The geography of insight : the sciences, the humanities, how they differ, why they matter - Foley, Richard, 1947- (Oxford University Press, 2018)
The Geography of Insight argues that the issues of the humanities and sciences are different in kind and that inquiries into these issues also have different characteristics as do the resulting insights. These differences constitute an intellectual geography of the humanities and sciences: a mapping of key features of the two domains.